2001
DOI: 10.1007/bf03016195
|View full text |Cite
|
Sign up to set email alerts
|

Éviter la salle de réveil, l’étude pilote d’un “protocole accéléré” dans un hôpital communautaire

Abstract: Purpose: To evaluate the effectiveness of short-acting anesthetic drugs and techniques to achieve recovery room bypass criteria after minor surgery in a community hospital environment.Methods: After agreement by a multidisciplinary committee, a pilot project was undertaken to assess the usefulness of ultra-short acting anesthetic drugs and pre-emptive analgesia to facilitate rapid recovery from general anesthesia. A cohort of 100 ASA I-II patients aged 18-65 yr undergoing simple knee arthroscopy or minor perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…The patients who achieved fast-track criteria did not increase operating room time, and were discharged home earlier. 12 However, patients in the fast-track group were not compared to conventional PACU admission, and the study was conducted in two institutions with different nursing and recovery settings.…”
Section: Fast-trackingmentioning
confidence: 99%
“…The patients who achieved fast-track criteria did not increase operating room time, and were discharged home earlier. 12 However, patients in the fast-track group were not compared to conventional PACU admission, and the study was conducted in two institutions with different nursing and recovery settings.…”
Section: Fast-trackingmentioning
confidence: 99%
“…Numerous studies have analyzed postanesthesia care unit (PACU) discharge procedures, focusing on factors that might or might not decrease PACU time [1][2][3][4][5][6][7][8][9][10]. Some of this work evaluated how the choice of anesthetic management could influence PACU time.…”
Section: Introductionmentioning
confidence: 99%
“…Some of this work evaluated how the choice of anesthetic management could influence PACU time. Several studies showed that the use of insoluble anesthetic agents and/or rapidly acting intravenous drugs such as propofol or remifentanil could significantly reduce PACU length of stay [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of a fast-tracking protocol in clinical anesthesia practice has been expected to improve the effectiveness and efficiency of an ambulatory facility by eliminating unnecessary delays in discharge and by decreasing PACU nursing workload and costs. In this issue of the Canadian Journal of Anesthesia, a study by Peter Duncan, et al 1 showed a possible cost-effective caseload handling following the implementation of a pilot fast-tracking protocol. This study is important since it is the first report of a successful practice in a community setting, which is more generalizable and applicable to community practitioners.…”
mentioning
confidence: 99%
“…L'application d'un protocole accéléré en anesthésie clinique devait améliorer l'efficacité et le rendement d'une unité ambulatoire en élimi-nant les délais inutiles à accorder le congé et en diminuant la charge de travail et le coût des soins infirmiers à la SR. Dans le présent numéro du Journal, une étude réalisée par Peter Duncan, et coll. 1 montre une prise en charge rentable du nombre de cas à la suite de la mise en oeuvre d'un protocole accéléré expérimental. Cette étude est importante, car c'est le premier compte rendu d'une pratique réussie dans un hôpital communautaire, donc plus facile d'en faire une application étendue parmi les médecins oeuvrant dans ce secteur.…”
unclassified